Gram‐Scale Preparation of Tri‐Coordinated Single‐Atom Catalysts for CO2 Electrolysis in Large‐Scale Membrane Electrode Assembly - Lei Yuan; Xin Li; Guilin Li; Kuilin Peng; Hongyu Zhang; Shaojuan Zeng; Xiaofu Sun; Xiangping Zhang (Advanced Science)
Abstract Accelerating the commercialization of CO2 electroreduction is essential for carbon utilization, yet it faces challenges of precious metal catalysts cost and scaling‐up of the corresponding devices. In this study, a low‐cost and tri‐coordinated single‐atom catalyst (SAC) with Ni‐N3 center is fabricated in gram‐scale using metal ionic liquids as precursor. The gram‐scale Ni‐N3 SAC (g‐NiN3) achieves efficient electroreduction of CO2 to CO (eCO2‐to‐CO) with a maximum Faradaic efficiency of 98.9% at 2.8 V in a 2 × 2 cm2 membrane electrode assembly (MEA) cell, and CO selectivity exceeds 90% during 100 h electrolysis at 100 mA·cm−2. Moreover, the g‐NiN3 is tested in a scale‐up MEA reactor (10 × 10 cm2), which can not only show 97.1% CO Faradaic efficiency with a reaction current of 6.07 A but also achieves a CO2 single‐pass conversion of 41.0%, corresponding to energy efficiency of the system as high as 43.1%. The overall performance of g‐NiN3 is one of the state‐of‐the‐art systems for eCO2‐to‐CO. In addition, the scale‐up device stably generates CO at a high rate of 12.0 L·kW·h−1 over continuous CO2 electrolysis. The techno‐economic assessment demonstrates that the eCO2‐to‐CO using g‐NiN3 can realize CO production cost of 1.08 $·kg−1, and shows great profitability prospects in the future.